Gerhana dalam Perspektif Hadis - Muhammad Razesh Musyarraf; Muhammad Alif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores the phenomenon of eclipses from the perspective of Islamic prophetic traditions (hadith), aiming to understand the theological and ritual responses to such celestial events in Islamic teachings. Despite being predictable astronomical occurrences, eclipses have often been associated with myths and superstitions in various cultures. The study investigates how Islamic teachings demystify these phenomena through authentic hadiths. Using a qualitative method with a thematic and historical approach, primary data were drawn from digital hadith sources such as Maktabah Syamilah, Hadith Soft, and the Encyclopedia of Hadith: The Nine Imams. The analysis identified ten relevant hadiths, which were grouped into three main themes: the meaning of eclipses, the spiritual wisdom behind them, and prescribed religious practices. Findings show that Islam emphasizes eclipses as signs of God's greatness, unrelated to death or birth events, and calls for reflective acts such as prayer and charity. This research contributes to the discourse on how religious texts provide a rational and spiritual framework for natural phenomena